A scenario approach for ecosystem-service changes. (February 2018) - Hasegawa, Yasuhiro; Okabe, Kimiko; Taki, Hisatomo
Highlights: The scenario approach been vital to reduce uncertainty for environmental policy decision-making. Analyzed 106 papers that addressed global and regional drivers of change and ecosystem services. Most papers of global/ regional ecosystem services used three scenarios and for the next 20–30 years at the basin or administrative unit level. Scenario studies were analyzed in four types of scenario: strategic, exploratory original, based on major report, and normative. Trends in scenario building related to environmental assessment are offered at the participatory, expert judgement, researcher. Abstract: Future predictions are imperative for environmental planning decisions as ecosystem changes take time to have an effect. In this paper, on the basis of a scenario approach to expose common frameworks and legitimacy, we quantitatively and qualitatively reviewed scientific papers to assess the future condition of ecosystem services. Of the 464 recent papers on biodiversity and ecosystem service changes, we extracted 106 papers by excluding papers that only examined climate change and/or carbon dioxide. Of the 106 papers, most used three scenarios to assess changes in from two to four ecosystem services over the next 20 to 30 years. Overall, not all of the scenarios were used in a predictive capacity, and of the ecosystem services examined, regulating and provisioning services were analyzed more frequently than cultural services. In practice, when using the outcomes of this scenario approach, either an administrative unit or a basin approach is an advisable scale for decision making. As a basin includes various micro ecosystems and various stakeholders, a participatory approach is the most favored.